1994
DOI: 10.2466/pms.1994.79.3.1259
|View full text |Cite
|
Sign up to set email alerts
|

Right-Left Orientation: Development of Correct Use of Right and Left Terms

Abstract: Right-left orientation includes discrimination and recognition as well as identification, the former two differentiating between symmetrical cues and the latter using the words right and left. In the present experiment involving 406 children, the evolution of the knowledge and use of the concepts of right and left were assessed. Discrimination and recognition on all tasks used in this study are mastered much earlier than verbal identification, and, at even 11 years of age, half of the subjects of the present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(60 citation statements)
references
References 11 publications
5
49
0
6
Order By: Relevance
“…These findings also do not reveal whether consistent spatial language and its resulting cognitive benefits can be acquired in adulthood. In typically developing children, acquiring either a spoken or signed language, spatial language is usually mastered after the age of four, later than many other aspects of language (36,37). A previous study with Nicaraguan signers reported that first-cohort signers' late acquisition of words like "think" and "know" predicted their subsequent theory-of-mind development in adulthood (38).…”
Section: Discussionmentioning
confidence: 99%
“…These findings also do not reveal whether consistent spatial language and its resulting cognitive benefits can be acquired in adulthood. In typically developing children, acquiring either a spoken or signed language, spatial language is usually mastered after the age of four, later than many other aspects of language (36,37). A previous study with Nicaraguan signers reported that first-cohort signers' late acquisition of words like "think" and "know" predicted their subsequent theory-of-mind development in adulthood (38).…”
Section: Discussionmentioning
confidence: 99%
“…Second, the relevant linguistic spatial relational constructions may be expected to be learned later by children. Again, the evidence suggests that this is correct: Children in cultures where absolute coding is predominant seem to master this system as early as 4 and certainly by 7 years of age (18,23,38), whereas children in relative-coding cultures do not seem to master full use of the left͞right systems until Ϸ11 years of age (24,37).…”
Section: Part 2: Phylogenetic Inheritancementioning
confidence: 99%
“…We started at 9 years old because younger children do not yet possess a fully mature knowledge of the words and concepts "left" and "right" (Rigal, 1994), which is a prerequisite for the task we used. We used the same task design as Gevers et al (2010, experiment 4), of which a graphical illustration is provided in Figure 1.…”
mentioning
confidence: 99%